(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
Peculiarities of structures of hydro technical structures technical condition are considered. The problem concerning normative documentation on the inspection of hydraulic structures is considered, and the absence of standards for the inspection of this type structures is revealed. The issue of hydraulic structures inspection by the example of a three-chamber lockin Zaporizhzhia city is considered. The issue of the deformed state according to observations of past years are considered. The recommendations for the further exploitation, repair and completion of reconstruction of a three-chamber lockin Zaporizhzhia are given.